Neurobrucellosis manifested by recurrent aseptic meningitis: A case report - Reza Razaghi; Fatemeh Kourkinejad_Gharaei; Forough Faroughi (IDCases)
Brucellosis is an endemic zoonotic disease in LMIC countries. Neurobrucellosis is a rare and serious complication that affects 3–5 % of cases worldwide. We report the successful treatment of a 31-year-old woman who presented with a chief complaint of headache and nausea. Headache was started six months before admission in the frontal and occipital area with radiation to the neck. The patient hospitalized three times within last six months with diagnosis of aseptic meningitis. Brucellosis, tuberculosis, and syphilis tests and CSF fluid analysis were requested. Neutrophilia and pleocytosis in CSF fluid. Analysis of CSF fluid for cytology and PCR test for HSV-1&2 was negative. Rheumatologic tests for SLE, Behcet's disease and sarcoidosis were also negative. Test results was as follow: Wright: 1/320, Coombs Wright: 1/640, 2ME: 1/160, Brucella IgG: 25(Positive). According to the test results, combined treatment with rifampin, Co-trimoxazole, and ceftriaxone was performed for neurobrucellosis for nine months. Considering the endemic prevalence of brucellosis in this region, the rare manifestations of this disease should be considered.